Diversification Potential of Asian Real Estate Investment Trusts: Evidence from Japan, Singapore and Hong Kong - Tsang, Lai Kwan Maggie (2010)
In this paper we examine the potential benefits by investing Asian REIT markets from both the local and foreign investors' perspectives. Mainly, the study has focused on REIT markets in Japan, Singapore and Hong Kong. By examining the relationship between REIT, domestic stock and bond market would capture the benefit of REIT investment within a multi-asset portfolio. The linkage of REIT markets in US, Japan, Singapore and Hong Kong form another main part of this paper. Investigation of the interrelationship between the REIT markets would make contribution to the international investors through better understanding of the diversification potential and the profitable investment strategy by investing Asian REIT markets. Johansen cointegration test and Granger causality analysis is utilized to explore the long-run and short-run relationship between the financial markets. The empirical findings show that there is no cointegration between REIT and domestic financial markets and also across the REIT markets. Granger causality tests show evidences that stock market lead the REIT market in all three Asian countries. Other findings from the causality test show that U.S. and Singapore REIT market have greater impact on other REIT markets. More importantly, we have observed a significant change of the short-term linkage between markets after the Subprime mortgage crisis in 2007.